2022
DOI: 10.1093/hmg/ddac089
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of pathogenic germline variants in cancer susceptibility genes in 1336 renal cell carcinoma cases

Abstract: Background Renal cell carcinoma (RCC) occurs in a number of cancer predisposition syndromes but the genetic architecture of susceptibility to RCC is not well defined. We investigated the frequency of pathogenic germline variants in cancer susceptibility genes (CSGs) within a large series of unselected RCC participants. Methods Whole genome sequencing data on 1336 RCC participants and 5834 controls recruited to the UK 100000 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…In the present study, the association remains significant even when correcting for multiple comparisons, likely due to the larger sample size. This association is further supported by studies of patients with kidney cancers in which CHEK2 PVs were overrepresented and found in 2%-3.5% of patients . More data on the prognosis of CHEK2 -associated kidney cancers including modeling and cost-effectiveness studies are needed to inform screening.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the association remains significant even when correcting for multiple comparisons, likely due to the larger sample size. This association is further supported by studies of patients with kidney cancers in which CHEK2 PVs were overrepresented and found in 2%-3.5% of patients . More data on the prognosis of CHEK2 -associated kidney cancers including modeling and cost-effectiveness studies are needed to inform screening.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to prior studies 9,11,12 , LOF variants in CHEK2 were not significantly enriched in ccRCC after excluding low-penetrance variants (OR: 1.01, CI: 0.41-2.52; p-value of 0.980, qvalue: 0.997) or nccRCC (OR: 2.82, CI: 1.13-7.05; p-value of 0.0536, q-value: 0.79). No other DDR genes were enriched with PVs in ccRCC or nccRCC patients compared to the cancer-free controls (eTables 7 and 8).…”
Section: Patientsmentioning
confidence: 62%
“…Attempts to demonstrate association by comparing frequencies of PVs in RCC cases against public databases such as ExAC 66 or gnomAD 56 are fraught with major technical limitations, including that the samples are likely not sequenced using the same sequencing platform, variants were not called using the same variant discovery pipeline and were not processed identically, and cases and controls were not ancestry-matched to ensure a robust statistical comparison. Recently, two studies leveraged case-control approaches to report an association of rare germline PVs in CHEK2 with an elevated risk of RCC 11,12 . However, both studies treated different subtypes of RCC together as a single phenotype and included CHEK2 variants with distinct population properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations